2011 IEEE International Conference on Multimedia and Expo 2011
DOI: 10.1109/icme.2011.6012199
|View full text |Cite
|
Sign up to set email alerts
|

Bit allocation for multiview image compression using cubic synthesized view distortion model

Abstract: "Texture-plus-depth" has become a popular coding format for multiview image compression, where a decoder can synthesize images at intermediate viewpoints using encoded texture and depth maps of closest captured view locations via depth-image-based rendering (DIBR). As in other resource-constrained scenarios, limited available bits must be optimally distributed among captured texture and depth maps to minimize the expected signal distortion at the decoder. A specific challenge of multiview image compression for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Studies presented in [23]- [25] target the optimal rate allocation problem such that the synthesized view distortion is minimized. Moreover, in [26], a relationship between the texture and depth quantization parameters (QPs) is estimated to simplify rate allocation.…”
Section: B Codingmentioning
confidence: 99%
“…Studies presented in [23]- [25] target the optimal rate allocation problem such that the synthesized view distortion is minimized. Moreover, in [26], a relationship between the texture and depth quantization parameters (QPs) is estimated to simplify rate allocation.…”
Section: B Codingmentioning
confidence: 99%
“…In previous work, Cheung [4] and Velisavljevic [6] derive a VVSD model with respect to the distance between virtual view and reference view, where Cheung takes a rough synthesis model to represent synthesis procedure, and Velisavljevic refines the synthesis model but fails to provide specific proofs for some observed features such as linearity of situation probability. Fang and Cheung [7] propose a VVSD model based on Power Spectral Density (PSD) and spatial analysis.…”
Section: Motivationmentioning
confidence: 99%
“…An autoregressive model was proposed by Kim et al [8] to estimate the synthesis distortion at the block level and was shown to be effective for rate-distortion optimized mode selection. A distortion model as a function of the view location was also proposed by Velisavljevic et al [9] for bit allocation. Takahashi [10] proposed an optimized view interpolation scheme based on frequency domain analysis of depth map error.…”
Section: Previous Workmentioning
confidence: 99%